Pengaruh Kompensasi, Beban Kerja, dan Motivasi Kerja terhadap Organizational Citizenship Behavior (OCB) pada Pegawai di Sekretariat DPRD Kabupaten Temanggung - Amanda Amelia; Nany Noor Kurniyati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the effect of compensation, workload, and work motivation on Organizational Citizenship Behaviour (OCB) among employees of the Temanggung Regency DPRD Secretariat. The method used is quantitative with a total sampling technique involving 35 respondents. Data collection was carried out by distributing questionnaires directly to respondents using a Likert scale research instrument. Data were analysed using SPSS version 25, with the following analyses conducted: validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing. The results of the study indicate that compensation (), workload (), and work motivation () together have a significant effect on OCB, with the calculated F value > table F value (13.074 > 2.84) and significance 0.000 < 0.05. However, partially, only work motivation has a significant effect with a t-value > t-table (4.237 > 2.040) and significance of 0.000 < 0.05. Meanwhile, compensation with t calculated < t table (0.561 < 2.040) and a significance value of 0.579 > 0.05 and workload with t calculated < t table (1.177 < 2.040) and a significance value of 0.248 > 0.05 did not significantly influence OCB. The coefficient of determination value of 55.9% indicates that the model can moderately explain OCB.